Current college graduates’ employability factors based on university graduates in Shaanxi Province, China - Jiang, Lijuan; Chen, Zirou; Lei, Changkui (Frontiers in Psychology, 2023)
With the development of higher education, there are a large number of college graduates turn into the labor market, college students’ employability has become a popular topic. In order to explore the factors that affect employability’s improvement and what factors employability includes, this paper summarizes the previous researches on employability, uses university graduates of Shaanxi Province as research example, investigates the employability factors of colleges graduates. With the help of SPSS software, data analysis is conducted on the 220 valid questionnaires. The study uses reliability and validity analysis to verify the quality of the questionnaire, takes the exploratory factor analysis to test the employability factors of college students, employs multiple linear regression analysis to test the factors that influence employability’s improvement. The results of the research show that individual traits, social experience and workplace training have a significant impact on college students’ employability; knowledge understanding and learning ability, self-management ability, emotional intelligence, generic skills, professional ability and career planning capability are the important factors of the employability which college students should master. Our research results update the influencing factors of employability, so that contemporary college students have a new understanding of employability, and help them to improve their employability more pertinently.